Work Praises the Master: The Concept of Work in Slovenia - Babič, Saša (Tautosakos darbai, 2026)
Short folklore forms, like proverbs and riddles with integrated metaphors and stereotypes, capture diachronic reflections of the surroundings, including the economic situation and societal values. The economy and economic activity as a dominant part of everyday life is a very important factor in family life. In contemporary ethnology, “everyday” is used to mean the “culture of the many”, the banal, widespread phenomena of culture. More broadly, it represents both the universal and the most one of a kind, the social and the personal spheres of life. Everyday life most faithfully reflects how life and the world are understood. This article focuses on the concept of work in everyday life and its representation in Slovenian short folklore forms, specifically proverbs and riddles, which are analysed across nine thematic groups. This ethnolinguistic study uses the proverb archive at the ZRC SAZU Institute of Slovenian Ethnology.
Keywords: short folklore form; proverb; riddle; work; everyday; Slovenian folklore